Fabrication and performance evaluation of a solar pond - BALAKRISHNAN A; Kavitha K.S; Er. V. R. Ramachandran (Guide) (Tavanur 1993 Department of Farm Power Machinery and Energy)
Fabrication and performance evaluation of a solar pond
Fabrication and performance evaluation of a solar pond